Effect of Neck Exercises Combined with Stimulating Baihui and Yongquan Acupoints Based on the Concept of Muscle and Bone Balance on Patients with Cervical Hypertension - CHEN Xiuming; LIN Jian; LIU Jinyong; FANG Yuelong; ZHAN Zhengxuan; HE Zhen; CAI Shuhe (康复学报)
ObjectiveTo observe the efficacy of neck exercises combined with stimulating Baihui (DU20) and Yongquan (KI1) acupoints based on the concept of muscle and bone balance on patients with cervical hypertension (CHBP ) of Yin deficiency and Yang hyperactivity.MethodsA total of 60 patients with CHBP of Yin deficiency and Yang hyperactivity were treated in the Affiliated Rehabilitation Hospital of Fujian University of Traditional Chinese Medicine from April 2017 to April 2020, which were randomly divided into the control group and the observation group, with 30 cases in each group. The control group was given conventional western medicine antihypertensive treatment, and the observation group was additionally given neck exercises combined with stimulating Baihui and Yongquan acupoints. Neck exercises mainly included four movements: forward neck flexion stretch, lateral neck flexion stretch, holding up hands and looking up, stretching hands backward and looking up. Each set of exercises included all the above movements. Patients completed three sets of exercises each time, three times a day, continous treatment for 14 days. Stimulating Baihui and Yongquan acupoints included head and neck scraping therapy and moxibustion of Yongquan acupoint, once every other day. It lasted for seven times. The systolic blood pressure (SBP) and diastolic blood pressure (DBP), visual analogue scale (VAS), neck disability index (NDI) score, TCM syndrome score, and the effective rate of antihypertensive were compared between the two groups before and after the treatment.ResultsThe SBP and DBP of both groups decreased significantly after the treatment, VAS score, NDI score and TCM syndrome score of the observation group decreased significantly after the treatment, the difference was statistically significant (P<0.05). Compared with the control group, SBP, DBP, VAS score, NDI score and TCM syndrome score of the observation group after the treatment decreased more significantly (P<0.05), and the total effective rate of antihypertensive of the observation group was significantly higher than that of the control group, the difference was statistically significant (P<0.05).ConclusionNeck exercises combined with stimulating Baihui and Yongquan acupoints based on the concept of muscle and bone balance can effectively reduce blood pressure and neck pain of CHBP patients with Yin deficiency and Yang hyperactivity, and improve cervical function, which is worthy of clinical application.